Implementasi Kebijakan Pemerintah dalam Kedisiplinan Aparatur Sipil Negara - Yudi Setiana; Tresia Kristiana; Kusnida Indrajaya (Journal Of Administration and Educational Management (ALIGNMENT), 2024)
This research aims to describe and analyze the implementation of disciplinary policies for the State Civil Apparatus within the Ministry of Religion of Sukamara Regency. This research was conducted using Field Research. The analytical technique applied describes and analyzes the implementation of disciplinary policies for State Civil Apparatus within the Ministry of Religion of Sukamara Regency. The research results show procedures or mechanisms for implementing discipline, sanctions, monitoring and evaluation, information, and complaints. Conclusion: All of these things support and inhibit factors in implementing government policies in the discipline. The procedures and mechanisms have been running well to support exemplary implementation in the Sukamara Regency Ministry of Religion. Keywords: State Civil Service, Government Policy, Discipline